An introduction to family social work - Collins, Donald; Jordan, Catheleen; Coleman, Heather (Empowerment series, 2013)
Suitable for students who work with families, but not necessarily continue with advanced family therapy training, this title provides a foundation in the concepts and skills necessary for success in the profession.